Land subsidence assessment on karst based on resistivity and geotechnical parameters - Muhammad Altin Massinai; Muhammad Fawzy Ismullah Massinai; Erfan Syamsuddin (Journal of Degraded and Mining Lands Management, 2023)
Karst is geomorphologically composed of limestone. However, limestone is very susceptible to weathering due to the influence of water, which can cause land subsidence. The resistivity method is often used to determine the potential for land subsidence, while geotechnical methods are commonly considered capable of juxtaposing with resistivity methods to support interpretation accuracy. The current research was conducted to determine the potential for land subsidence in the karst area in Lappae, South Sulawesi, Indonesia. The resistivity method utilizes a dipole-dipole configuration, and the geotechnical parameters used are uniformity coefficient, curvature coefficient, water content, shear angle, and cohesion. The results obtained can be classified into northern and southern areas. The classification of these areas is based on the resistivity results, which show very high resistivity values        (> 4800 Ωm) in the southern part. This value is assumed to be a feature of the cave. Caves are predominantly distributed in the southern part. The five geotechnical parameters show that the northern part, which was composed of massive limestone (150-1600 Ωm), is a stable area, though it is highly prone to landslides. As for the southern part, geotechnical parameters suggest that the presence of caves is the primary factor contributing to the very high potential for landslides in this region. These results indicate that, based on the evaluation of this location, it is not feasible for land use. In addition, in spite of the low cost and rapid methods, the combination of these methods shows good results.